Sports Orthopedics - Hazzaa Walaa Eldin A; 2; Mattes K (Dynamic Media Sales Verlag, 2019)
Running is a simple and inexpensive way to lose weight and improve cardiovascular fitness. It has been argued that barefoot running can be considered as a natural alternative to the traditional run with athletic shoes in recreational athletes.The aim of the study was to investigate the effect of foot strike patterns and local muscle fatigue of the plantar and dorsiflexors on plantar pressure distribution and the selected kinematic characteristics when running barefoot on the treadmill at three speeds. 26 voluntary forefoot and rearfoot runners of similar age and body mass participated in the study. Each group completed two tests, with a time interval of 3-7 days. The kinematic data were taken with the help of the three-dimensional measuring and analysis system while running on the treadmill. The fatigue protocol included the isometric maximal force test and an isokinetic endurance test. In order to check the differences, variance analysis with repeated measurements was used. The strength values of the two groups of runners showed significant differences in the plantar flexors in the endurance test and in the fatigue index on average, for both the left and the right legs. The results of the strength values are surprising, because the plantar flexors of this group of runners should be well-trained due to the forefoot preference during regular running. The pressure maxima reduced under the exposed foot regions after fatigue, which mean under the forefoot at forefoot strike and under the heel at rearfoot strike. The two groups of runners differed in foot angle at Foot on with higher values of the forefoot runners. The greater foot angle of the forefoot runner improved the shock absorption and thus can reduce the risk of injury. KEY WORDS: Fatigue, Foot Strike, Kinematic, Maximal Force Test, Endurance Test